These will be removed by our Editorial Office. Аssessment of the effectiveness of hodgkin’s lymphoma treatment in children using 18F-FDG PET-CT: А clinical case (Herald of the National Children's Medical Center, 2025)
Aim. To evaluate the effectiveness of Hodgkin’s lymphoma treatment in children by conducting a PET/CT scan with 18F-fluorodeoxyglucose (18F-FDG) after chemotherapy courses, based on a clinical case.Materials and methods. The study utilized a clinical case analysis to evaluate the effectiveness of Hodgkin’s lymphoma treatment in a child using positron emission tomography combined with computed tomography (PET/CT) with 18F-fluorodeoxyglucose (18F-FDG). The approach consisted of an initial PET/CT scan to determine the disease stage and extent of involvement before treatment, followed by courses of chemotherapy and a subsequent PET/CT scan to assess the therapeutic response. The Deauville scale was used to standardize the interpretation of the results and to assess the metabolic activity of the tumor.Results. The initial PET/CT scan on October 16, 2024, revealed extensive involvement of Hodgkin’s lymphoma, affecting the supraclavicular, mediastinal, and abdominal lymph nodes, as well as both lungs; this condition was rated as 5 points on the Deauville scale, indicating high metabolic activity. After courses of chemotherapy, a follow-up PET/CT scan on December 18, 2024, documented a complete metabolic response, as the pathological isotope uptake in the previously affected areas was no longer observed, and the result was rated as 1 point on the Deauville scale.Conclusion. The presented clinical case demonstrates the high informational value and clinical significance of PET/CT with 18F-FDG in assessing the effectiveness of Hodgkin’s lymphoma treatment in children. This technique is the "gold standard"for evaluating therapeutic response in this disease and allows for the timely and accurate determination of a complete metabolic response. This, in turn, makes it possible to reduce the toxic burden on a growing organism by avoiding unnecessary radiotherapy and modifying treatment regimens, which ultimately improves the patient’s quality of life and chances of recovery. Therefore, the widespread implementation of PET/CT in pediatric oncology should be a priority for modern diagnostic standards.
Keywords: Hodgkin’s lymphoma; PET/CT; 18F-FDG